Sistem Pengamanan Lukisan Digital Menggunakan Metode Rivest Shamir Adleman (RSA) - Putra Anga Biara, I Dewa Gde; Hendra Suputra, I Putu Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 11 No 4 (2023): JELIKU Volume 11 No 4, May 2023DO - 10.24843/JLK.2023.v11.i04.p05, 2023)
Digital painting is a result of the process of making digital images/paintings using digital brushes that can produce lines. This painting has become a modern art that can be disseminated through the internet. However, with the ease of disseminating information, digital artwork on the internet is very easy to fake or steal. To solve this problem, a system was created to secure digital painting files using the Rivest Shamir Adleman (RSA) encryption and decryption method. RSA has the basis for encryption and decryption, namely the concepts of prime numbers and modulo arithmetic. Both keys are integers. Based on the research conducted, digital painting files are converted into text and then will go through an encryption process by RSA into text files. Furthermore, to restore the encryption results, the decryption process is carried out with the private key. The weakness of the current system is its inability to process large image files.